Transcultural adaptation and validation of the Conditions of Work Effectiveness - Questionnaire-II instrument - Elizabeth Bernardino; Ana Maria Dyniewicz; Kaoana Lima Botto Carvalho; Luisa Canestraro Kalinowski; Wagner Hugo Bonat (Universidade de São Paulo, 2013)
OBJECTIVE: This study aims at translating and validating the content of the instrument Conditions of Work Effectiveness - Questionnaire-II (CWEQ-II), developed by Laschinger, Finegan, Shamian and Wilk, modified from the original CWEQ for the Brazilian culture. METHOD: the methodological procedure consisted of the stages of translation of the instrument into the Portuguese language; back-translation; semantic, idiomatic and cultural equivalence and tests of the final version. The instrument in the Portuguese version was applied to a group of 40 nurses in two hospitals. RESULTS: the data resulted in a Cronbach's Alpha of 0.86 for the first hospital and 0.88 for the second one. The results of the factorial analysis are considered sufficiently satisfactory. CONCLUSION: It is to conclude that the instrument can be used in Brazil.